Revolutionizing Food Security, Industrial Growth, and Agricultural Sustainability through Technological Advancements: A Comprehensive Research Analysis - Imtiaz, Ahsan; Zakir, Fahad; Fatima, Noroze (Annals of Human and Social Sciences, 2024)
Food processing, as a transformative process, plays a pivotal role in shaping the nutritional composition of food. The persistent menace of climate change poses a global threat, particularly impacting food security in developing nations and exerting its influence on crop productivity even in well-established regions. The multifaceted and intricate consequences of these ongoing climatic shifts significantly affect both food availability and population health. Consequently, there is a pressing need for a science-driven approach that can adeptly harness the opportunities presented by evolving environmental conditions to enhance food productivity and ensure security. The imperative for safe technological innovations becomes evident in advancing the realization of sustainable development goals (SDGs), particularly Zero Hunger. This study employs a literature review methodology to investigate the consequences of food security issues and also find out the best possible approaches to cover the maximum area to fertilize. Using a literature review methodology, the research highlights the importance of science-driven approaches and technological innovations in mitigating these impacts and advancing sustainable development goals, particularly Zero Hunger. The findings underscore the need for advanced food processing techniques, investment in research, supportive policies, capacity building, and collaboration to improve food availability and nutrition. Ultimately, the conclusions drawn from this research emphasize a positive correlation between safe food processing practices and achievement.